J.P. and the STINKY MONSTER - Crespo, Ana, 1976-; Sirotich, Erica (New York, NY : AV2 by Weigl, 2019)
A boy pretending to be a dog experiences jealousy when he competes with his new baby cousin for Grandma's attention. Includes tips for parents and teachers on ways to help a child work through jealousy.
"Mood-o-meter, jealous"--Front cover.
First published in 2016 by Albert Whitman & Company
Keywords: Jealousy -- Juvenile fiction; Babies -- Juvenile fiction; Grandmothers -- Juvenile fiction; Imagination -- Juvenile fiction; Fiction